Upaya Meningkatkan Kemampuan Public Speaking Remaja Putri Di Panti Asuhan Hanifa III Kampuang Menggunakan Bimbingan Kelompok Dengan Teknik Diskusi - Nelani Khairun; Dodi Pasila Putra (FKIP, Universitas Palangka Raya, 2024)
Teenagers who are agents of change usually have various creative ideas and opinions that can provide positive change for world change. However, many teenagers do not dare to express their opinions to the public or in discussion forums because they do not have public speaking skills or speaking in public. Therefore, the researcher wants to try to improve public speaking skills, especially in this case, namely young women at the Hanifa III Village Orphanage using group guidance with discussion techniques. This research uses descriptive qualitative research methods with data collection techniques in the form of interviews and observations as well as data analysis techniques in the form of data reduction and data verification by summarizing all the research findings obtained. The results of this research show that efforts to improve the public speaking skills of young women at the Hanifa III Kampuang Orphanage using group guidance with discussion techniques have proven successful. Group guidance using discussion techniques made young women at the Hanifa III Kampuang Orphanage make them more courageous and confident in speaking to express their opinions in public.